2017
DOI: 10.1371/journal.pntd.0005420
|View full text |Cite
|
Sign up to set email alerts
|

Single locus genotyping to track Leishmania donovani in the Indian subcontinent: Application in Nepal

Abstract: BackgroundWe designed a straightforward method for discriminating circulating Leishmania populations in the Indian subcontinent (ISC). Research on transmission dynamics of visceral leishmaniasis (VL, or Kala-azar) was recently identified as one of the key research priorities for elimination of the disease in the ISC. VL in Bangladesh, India, and Nepal is caused by genetically homogeneous populations of Leishmania donovani parasites, transmitted by female sandflies. Classical methods to study diversity of these… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 22 publications
(32 reference statements)
0
17
0
Order By: Relevance
“…This is different to several previous transmission models of VL [ 18 20 ], which assume that individuals who have recovered from symptomatic or asymptomatic infection return to being susceptible after a number of years, and thus can be reinfected. Whilst this may be true for asymptomatic infection, multiple VL episodes are relatively rare [ 25 ] and the limited available evidence suggests that the majority of these are due to relapse rather than reinfection [ 65 , 66 ]. PKDL cases are also not included, since there were only 4 confirmed cases of PKDL during the study period and no information was recorded on time of PKDL onset.…”
Section: Methodsmentioning
confidence: 99%
“…This is different to several previous transmission models of VL [ 18 20 ], which assume that individuals who have recovered from symptomatic or asymptomatic infection return to being susceptible after a number of years, and thus can be reinfected. Whilst this may be true for asymptomatic infection, multiple VL episodes are relatively rare [ 25 ] and the limited available evidence suggests that the majority of these are due to relapse rather than reinfection [ 65 , 66 ]. PKDL cases are also not included, since there were only 4 confirmed cases of PKDL during the study period and no information was recorded on time of PKDL onset.…”
Section: Methodsmentioning
confidence: 99%
“…WGS offers unprecedented insight into the molecular epidemiology of Leishmania , in particular in the context of DR. As such, this method should be implemented in surveillance schemes, when and where it is available. Of course, molecular tracking could be simplified and new assays translated from this genomic knowledge, as seen with the single locus genotyping (SLG) for the detection of ISC groups [ 63 ] or a PCR assay for the detection of the 2-nt insertion in AQP1. However, such targeted assays do have limitations.…”
Section: Molecular Epidemiology Of Dr In L mentioning
confidence: 99%
“…However, such targeted assays do have limitations. For example, when SLG was evaluated in Nepal, about 50% of the isolates could not be typed, possibly because other genotypes circulating in this region are not detected by SLG [ 63 ].…”
Section: Molecular Epidemiology Of Dr In L mentioning
confidence: 99%
“…donovani (called ISC1), which diverged much earlier than 1850 ( Imamura et al, 2016 ). Rai et al (2017) investigated the geographic spread of different L . donovani genotypes over a period of 12 years (2002–2014) in Nepal and showed that the frequency of ISC1 was increasing in the country and that this emerging genotype was also present in the lowlands.…”
Section: Introductionmentioning
confidence: 99%